Analisis Pengambail Alihan Tata Ruang Pantai Carita Kabupaten Pandeglang Untuk Mendukung Penanggulangan Bencana Tsunami - Anwar - Kurniadi (Jurnal Ketahanan Nasional, 2022)
The terrible effects of the tsunami disaster in 2018 are almost all damage to infrastructure and environment in the recreation location of Carita Beach. Therefore, it needed to rearrange Carita Beach spatial.This research used method descriptive qualitative. This research analyzes the alternative reasons of Pandeglang Regency to taking over the spatial management of Carita beach to support Tsunami Disaster management.The results of the research were 1) the factors of supporting were old local government regulation based on this research were not suitable anymore and unable to prevent the terrible impact of the tsunami disaster, but with using the regional autonomy authority, the local government has a chance to take over the arrangement of spatial management of Sunda beach; 2) the factor of obstacles were special economic zone area of the central government in Sunda beach and different perception about the authority to manage Carita beach with Province of Banten; 3) the reason of alternatives for taking over were the terrible impact of tsunami disaster to defense and state security, precede the participation of the community in the development program, local government has the authority to give penalty and punishment to the inappropriate use. The conclusion was the local government of Pandeglang Regency makes taking over for rearrangement of the spatial of Carita beach because of relation to regulation and on the fact that the central government could not control it.